Estimation of land use conflicts due to the dynamic of african palm cultivation using remote sensing in cesar, colombia (2014)
Evaluation methods are presented to identify land use conflicts in Cesar, Colombia, due to African Palm crops. The seeding dynamics of palm are evaluated over several periods to determine if it has displaced more suitable land uses, occupied protected areas, or substituted forest ecosystems. The main intention is to resolve any doubts and corroborate declarations about the establishment of this species. The localization, extension, and growth of palm crops were determined through remote sensing and spatial analysis, as well as the land use conflicts. Recommendations are given to the scientific community and to palm growers. Although minimal, unsuitable land uses due to seeding of palm mainly present conflicts with the underutilization of moderately fertile land and the invasion of water protection areas.